White light emission from Eu3+, Tb3+ ions and ZnO nanocrystals embedded in SiO2 film - Khor, Kai Sherng (Nanyang Technological University, 2020)
This work serves as a continuation of a previous study done. In that study, a new method was researched into to produce white light emission from Zinc Oxide nanocrystals (ZnO-nc), Europium (Eu3+) RE ions, and Terbium (Tb3+) RE ions in a Silicon dioxide (SiO2) substrate. An excitation source of a single wavelength is required to achieve this instead of 3 different wavelengths. This is possible as only the ZnO-nc is excited by the excitation source. The two RE ions are excited by the energy transfer from ZnO-nc when it de-excites. The red, green, and blue emissions from the 3 constituent materials results in the production of white light. In fact, any colour in the International Commission on Illumination (CIE) colour space is theoretically achievable. This work improves on the previous study by finding a quicker and more efficient method of predicting the concentration of the RE ions required to be doped to a constant ZnO-nc concentration to produce a sample with emission of any desired colour. 2 models were used to achieve this, namely the power series model and the multivariate adaptive regression splines (MARS) algorithm. Both models have some variations in results as compared to the previous study, possible due to the lack of sufficient training data. However, they proved that it is possible to achieve a faster and more efficient method. Improvements on these models could bring about a system that allows for the accurate fabrication of a sample for any desired colour.